Joseph A. Schumpeter a theory of social and economic evolution - Andersen, Esben Sloth (New York Palgrave Macmillan, 2011)
"This book examines Schumpeter's dramatic theory of social and economic evolution as the pivot of his life and work. His theory emerged through a new combination of neoclassical economics, the historical school, and elite theory. It permeated not only his account for economic growth and development but also his studies of the routinised economy, business cycles, capitalism, the democratic system, and the evolution of economics. The book's comprehensive account resolves apparent paradoxes and clarifies Schumpeter's challenges to economists and other socialscientists".
Includes bibliographical references (pages 256-264) and index.
Keywords: Schumpeter, Joseph A. -- 1883-1950.; Economists -- United States -- Biography; Economists -- Austria -- Biography; Economics -- History -- 20th century; Economic history; Neoclassical school of economics